JOB SATISFACTION AMONG ARTS AND SCIENCE COLLEGE FACULTY MEMBERS IN TENKASI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
When employees have a positive perspective on their jobs and their personal lives, they are said to be enjoying job satisfaction. Job dissatisfaction generally reflects a negative attitude at work. The majority of views about specific employment aspects make up the collection of job satisfaction. The study's primary objectives are to describe the socio-economic status and measure the degree of workhappiness among the faculty members working in colleges of arts and sciences, 150 faculty members who work in the Tenkasi district provided the data for this study.